Combined maternal-associated risk factors with intrapartum fetal heart rate classification systems to predict peripartum asphyxia neonates. (November 2017) - Pruksanusak, Ninlapa; Thongphanang, Putthaporn; Suntharasaj, Thitima; Suwanrath, Chitkasaem; Geater, Alan
Abstract: Objective: To improve the predictive ability for identification of peripartum asphyxia neonates by using the 3-tier and 5-tier fetal heart rate (FHR) classification systems. Study design: A retrospective case-control study comparing peripartum asphyxia neonates and no asphyxia neonates was conducted. The FHR tracings were classified into the 3-tier and 5-tier systems by the two reviewers. Pearson's X 2 or Fisher's exact tests was used for comparisons between the groups. Logistic regression models were used to identify factors associated with peripartum asphyxia neonates. Odds Ratios (OR) and Likelihood Ratios (LR) with 95% confidence intervals (CI) were calculated from the regression coefficients. Results: A total of 36 peripartum asphyxia fetuses (5.0%) were enrolled. Overall, the performance of category II and suspicious tracings to detect peripartum asphyxia neonates was higher than the yellow and orange tracings with 61% and 67% sensitivity, respectively. The 5-tier FHR classification had higher specificity than the 3-tier system (82–99%). The predictive ability to detect peripartum asphyxia neonates by the 5-tier FHR classification was highest when combined with maternal-associated risk factors (AUC 0.67–0.72). Conclusion: Maternal-associated risk factors combined with an abnormal 5-tier FHR classification had high predictive ability and specificity to detect peripartum asphyxia neonates.